Spatial Relationship between Schools Population and Book Related Services in Skopje - Netkovska, N; Mirceva, Georgina; Naumoski, Andreja (IEEE, 2022)
During these pandemic times, people are bored with digital devices and reading digital books, and more and more they want to get a hand on real printed books. This is even more true, when it comes for high school kids, that most of the time they are spending in front of digital devices. In this direction, our paper project focuses on the investigation of the spatial relationship between high schools’ population and book related services, mainly photocopying and large printing services. Using GIS software we will present a spatial model map of the gathered data, not only on the location of these objects, but also the number of secondary school kids, different types of services provided by the book related services as well as the rating score for each store in specific radius. The interpolation spatial map with combination of the ring buffer analysis, provides useful insight into possible improvement for new business opening locations of these services. In future we plan to further advance this analysis by providing more associated objects and their properties related to book services.
Keywords: ArcGIS , School population , Photocopiers , Large printing services , Interpolation , Multiple Buffer Rings